Curcumin and its therapeutic potential in inflammatory bowel disease: A systematic review (Research, Society and Development, 2026)
Inflammatory bowel diseases (IBDs), such as Crohn's disease and ulcerative colitis, are chronic conditions characterized by persistent inflammation of the gastrointestinal tract, generating functional and psychological impacts on patients' lives. In this context, an alternative that has been widely studied in relation to treatment and diagnosis is the compound *Curcuma longa*, especially for its therapeutic potential related to its anti-inflammatory, antioxidant, and immunomodulatory properties. This systematic review aimed to gather and analyze recent scientific evidence on the effects of curcumin in the treatment of IBDs. Eighteen articles published between 2020 and 2025 in the PubMed, SciELO, and Virtual Health Library (BVS) databases were selected, evaluating the efficacy of curcumin alone or combined with piperine. The results demonstrated significant benefits in reducing intestinal inflammation, clinical improvement of symptoms, and a favorable safety profile. However, limitations such as low bioavailability and methodological heterogeneity among the studies indicate the need for more controlled clinical trials. Curcumin shows promise as an adjunct treatment for IBDs, provided its use is guided by robust evidence and professional monitoring.